Reducing Seniority Attitudes Among Middle School Students Through Group Guidance with Reframing Techniques - Febri Adhari Syahwitri; Yenti Arsini (Journal of General Education and Humanities, 2025)
The attitude of seniority among students in junior high schools (SMP) is a form of dysfunctional social relations that can disrupt an inclusive and healthy learning climate. This study aims to test the effectiveness of group counselling services using reframing techniques to reduce seniority attitudes among eighth-grade students at SMP Negeri 2 Silangkitang. The approach used is quantitative with a one-group pretest-posttest design. A sample of 9 students was purposively selected based on indications of seniority behaviour. The intervention was conducted over five sessions of group counselling that integrated reframing techniques to reshape participants' mindsets regarding the meaning of social leadership in the school context. The data collection instrument is a Likert scale questionnaire that measures the dimensions of social dominance, symbolic intimidation, and recognition of class status. Data analysis uses the Wilcoxon Signed-Rank test due to non-normal data distribution. The results show a significant decrease in seniority attitude scores, from a pretest average of 99.89 to 50.89 in the posttest, with a significance value (p) = 0.004 (p < 0.05). These findings indicate that reframing techniques are effective in helping students to reinterpret their social roles more constructively, thereby reducing dominant behaviour towards other students. This research contributes to developing educational counselling services as a preventive and curative strategy in building an equal, empathetic, and supportive school climate.